INTEGRASI AL-QUR’AN DAN SAINS DALAM PEMBELAJARAN AL-QUR’AN DAN SAINS MODERN DI SMA TRENSAINS MUHAMMADIYAH SRAGEN JAWA TENGAH - Romelah; Saputra, Iyus Herdiana; Hakim, Nur (LPPM STAI Muhammadiyah Probolinggo, 2024)
This study aims to determine the curriculum at SMA Trensains and describe the application of the integration of the Qur'an and science as well as strengthening the integration of the Qur'an and science at SMA Trensains Muhammadiyah Sragen, Central Java. This research is a qualitative field research taking the background of SMA Trensains Muhammadiyah Sragen, Central Java. The results showed that: (1) The curriculum of SMA Trensains is the Unification Curriculum. The Unification Curriculum is a curriculum that combines Science and Islam, Science based on the Quran, the science pesantren curriculum is a collaboration between Quranic material, science material, and language material. In its implementation, the three materials are integrated in pesantren activities for 24 hours. (2) The application of the integration of the Qur'ān and science is carried out through learning with an emphasis on 5 subjects, namely natural science, philosophy of science, Qur'an-hadith, language, and muhammadiyahan studies. (3) Strengthening the integration of the Qur'an and science through natural science deepening programs, including research and observation activities, fismath camp, tahajud physics (midnight), mipa club, guidance of Olympic athletes, public lectures and motivational seminars and training Keywords: Integration of Qur'an and Science ;Application of Integration ; Strengthening of Qur'an and Modern Science.